Structural modeling The effect of academic hope on Academic involvement with the mediating role of academic self-efficacy - Ali Vazirimehr; Samaneh Salimi (مطالعات روانشناسی تربیتی, 2021)
The present research set to evaluate the structural modeling of academic hope on academic involvement with the mediating role of academic self-efficacy conducted by correlational model and SEM. The statistical population consisted of the first-grade nomad high school students of Sistan and Baluchistan province in 2019-2020; 300 individuals were selected as a research sample using From Krejcie and Morgan's table, they were selected as a stratified random sample. Khormaei and Kamari's academic self-efficacy questionnaire (2017), Ryu Tisang's academic involvement (2011), and the academic self-efficacy questionnaire of Migli et al. (2000) were used to collect data. The questionnaire structure validity was calculated and confirmed using confirmatory factor analysis. The questionnaire reliability was obtained at 0.83, 0.90, and 0.85 using Cronbach’s alpha coefficient, respectively. Data was analyzed by Lisrel software. The results showed that academic hope had a direct effect on academic engagement (B = 0.55), academic hope had a direct effect on academic self-efficacy (B = 0.59), academic hope on academic engagement with the mediating role of academic self-efficacy had an indirect effect (B =26/0). According to the findings, the high academic hope level of nomad students has an effective role in their academic involvement. It is recommened to design and execute some plans to increase students’ academic hope.